A Microneedle-Microplate Platform to Detect Biomarkers in the Skin - Rachael Victoria Dixon; Wing Man Lau; Keng Wooi Ng (University of Huddersfield Press, 2022)
This research aimed to integrate an established signal quantification technique with immunocapture microneedle arrays (MNAs) to improve biomarker-based disease diagnostics in the skin. In this miniaturized sandwich enzyme-linked immunosorbent assay (ELISA) platform, the capture antibody was immobilised onto the surface of microneedles which, when inserted superficially into porcine skin, captured endogenous porcine immunoglobulin G (IgG) intradermally. Signal development was achieved by incubating the microneedles into-phenylenediamine (OPD) solution in a 384-well microplate and measuring the absorbance in a microplate spectrophotometer at 450 nm. This technique allows for rapid biomarker detection with high-throughput processing. Immunocapture microneedle devices such as these can be easily adapted for targeting different biomarkers or multiplexed leaving plenty of scope for future work and assay optimisation.